Determinan Profitabilitas Perusahaan Pertambangan Pada Indeks Saham Syariah Indonesia - M. Maulana; Weri Mahendra; Lili Purnama (LPPM ISNJ Bengkalis, 2022)
This study aims to assess the effect of firm size, liquidity, leverage efficiency, and working capital turnover on firm profitability. The study population is mining companies listed on the Indonesian Islamic Stock Index (ISSI) from 2016 to 2020. The total sample is 12 companies selected through the purposive sampling method. This study uses secondary data by collecting documentation data through the Indonesia Stock Exchange (IDX) website. The technique used is panel data regression. The study results show that the company's efficiency and size have a positive and significant effect on profitability. However, working capital turnover has a negative and significant effect on profitability. Meanwhile, liquidity and leverage have no significant effect on profitability. This study can complement existing studies and become a reference for investors and companies in determining the company size, capital turnover, and company efficiency in making investment decisions.